2021
DOI: 10.3390/act10070153
|View full text |Cite
|
Sign up to set email alerts
|

Design Method of Bearingless Permanent Magnet Slice Motor for Maglev Centrifugal Pump Based on Performance Metric Cluster

Abstract: Different from ordinary AC machines, the design of a bearingless permanent magnet slice motor (BPMSM) considers not only the torque performance, but also the passive and active suspension properties. In addition, BPMSM for a maglev centrifugal pump has unique design characteristics due to the integration of the pump head and sensors. This paper investigates evaluation and design techniques based on a cluster of performance metrics targeting on developing BPMSM for a maglev centrifugal pump. The cluster of perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A 3D model of the motor axial restoring force was used because the iron stator is composed of 12 discrete arms, and the interaction of these arms could not be modeled accurately using a simplified approach. 23 In contrast, a 2D FEA modeling approach for the motor torque was sufficiently robust to characterize the flux path and back iron thickness. 24 These flux density plots showed the distribution of magnetic flux following expected trends.…”
Section: Discussionmentioning
confidence: 99%
“…A 3D model of the motor axial restoring force was used because the iron stator is composed of 12 discrete arms, and the interaction of these arms could not be modeled accurately using a simplified approach. 23 In contrast, a 2D FEA modeling approach for the motor torque was sufficiently robust to characterize the flux path and back iron thickness. 24 These flux density plots showed the distribution of magnetic flux following expected trends.…”
Section: Discussionmentioning
confidence: 99%
“…Some fields, such as aerospace, medical, self-driving, etc., will suffer huge losses and irreversible results upon software faults. 14 Previous studies identified negative designs based on Java static code metrics for most Android apps, as they are typically developed in Java/C++. 15,16 In essence, these studies still work for Android apps, but Android features distribute smells differently, 17 and some specific code smells are more frequent.…”
Section: Code Smell In Androidmentioning
confidence: 99%
“…Limited research has been carried out to determine the general relationship between specific geometric features and performance characteristics unique to BPMSMs. A notable exception is the study by Zhang et al where they demonstrate the impact of three different geometric features on a configuration's performance characteristics [24]. This study, however, only focuses on a two-phase configuration and does not offer a comparison to those with different amounts of phases.…”
Section: Introductionmentioning
confidence: 99%